Characteristics and specifications of dashboards developed for the COVID-19 pandemic: a scoping review. - Khodaveisi, Taleb; Dehdarirad, Hossein; Bouraghi, Hamid; Mohammadpour, Ali; Sajadi, Fereydun; Hosseiniravandi, Mohammad (Journal of Public Health: From Theory to Practice (2198-1833), 2024)
Aim: The use of information-based solutions such as dashboards is on the rise for taking fact-based actions against the COVID-19 crisis. This scoping review aimed to comprehensively investigate COVID-19 dashboards from different technical perspectives. Subject and methods: Three main bibliographic databases, PubMed, Web of Science, and Scopus, were searched on 28 August 2021 to retrieve relevant studies. Arksey and O'Malley's (Int J Soc Res Methodol 8(1):19–32, 2005) methodological framework and the enhanced version of this methodology developed by Levac et al. (Implement Sci 5(1):1–9, 2010) were adopted for conducting this review. Results: In total, 26 articles were included. The COVID-19 dashboards mainly focused on the infected (n = 25), deceased (n = 17), and recovered cases (n = 13), as well as the performed test (n = 10). Most of the dashboards were interactive, with public accessibility targeting various user groups. While some dashboards were both informative and supportive (38%), most were mainly informative (92%). The dashboard data were generally analyzed using simple techniques (58%) and delivered through web-based applications (88%). Conclusion: Dashboards can help immediately manage, analyze, and summarize a huge amount of information about a COVID-19 outbreak. The findings revealed that the developed COVID-19 dashboards share more or less analogous characteristics that could lay the groundwork for designing and developing dashboards for any other pandemic.